The Effect Of Price, Ease Of Use, And Promotions On Consumer Decisions In Using Grabfood - Ilahi, Firman Rama Nur; Handayani, Sri; Abi, Yudi Irawan (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The purpose of this study is to determine whether price, ease of use, and promotion have a significant impact on consumer decisions in using GrabFood in Bengkulu City. This study uses a quantitative method and a sample size of 100 respondents. The data obtained was then processed using the SPSS application. The results of the multiple linear regression analysis are as follows: Equation Y = 2.836 + 0.264 X1 + 0.210 X2 + 0.519 X3 + 1.610. This describes a positive regression direction, meaning that the variables of Price, Ease of Use, and Promotion have a positive effect on Consumer Decisions in Using GrabFood (Y) in Bengkulu City. The coefficient of determination value from R square is 0.866. This means that the values of Price (x1), Ease of Use (x2), and Promotion (x3) affect Consumer Decisions in Using GrabFood (Y) by 86.6%, while the remaining 13.4% is influenced by other variables not examined in this study. The t-test results show that the calculated t-value is greater than the t-table value of 1.984. The f test results show that the significant F value is less than 0.05 and the F count is greater than the F table, namely 46.215 > 2.70, so the variables of Price (x1), Ease of Use (x2), and Promotion (x3) have a significant effect on Consumer Decisions in Using GrabFood (Y) in Bengkulu City.